THE CONCEPT OF LEGAL CONSCIOUSNESS AND ITS SOCIAL AND PHILOSOPHICAL ASPECTS - Soliev Umidjon Xusanovich (Galaxy International Interdisciplinary Research Journal, 2021)
Like many concepts, the concept of legal consciousness has been the focus of scientific research.In particular, the coverage of its socio-philosophical features is important in today’s era of globalization. This article discusses this.